O impacto das métricas de audiência na rotina de produção jornalística dos portais Uol e Estadão - Escaleira, Carla Fernandez (2020)
Based on a scenario of transformation in the journalistic content’s consumption and production, driven by the advancement of information and communication technologies (ICTs), this dissertation analyzes the application of audience metrics on UOL and Estadao’s websites content production routine. The study provides an overview of digital journalism consolidation, besides content production routine and the theory of newsmaking, as well as highlighting the state of art of the journalism audience metrics; it analyzes the creation of specialized areas in the newsroom to interpret the data generated by the metrics and also observes how the information generated by these tools may influence the relevance of the articles focused on public interest. Therefore, the research is qualitative and divided into literature review, description of the objects of study and analysis of the content of the in-depth interviews with websites’ journalists and digital communication experts. Finally, the study shows that the metrics are integrated into the journalistic production routine and the newsrooms have undergone changes to adapt to the new media ecosystem, which can be observed in the digital transformation process implemented by Estadão and also in the migration UOL’s audience team for the vehicle’s Metrics and Strategy Management. Among the results, the dissertation also reveals other changes in the content production routine that were driven by the use of metrics, as the new formats and dynamics of the agenda meetings and also conduction trainings for teams to use audience tools in their daily life. Thus, based on the interviews, the research reinforces that the metrics caused transformations in journalistic routines, but are additional tools and are not the exclusive factor for the generation of content in the studied vehicles.